Endotoxaemia and acute pancreatitis: correlation between the severity of the disease and the anti-enterobacterial common antigen antibody titre. Issue 10 (October 1984) - Kivilaakso, E; Valtonen, V V; Malkamäki, M; Palmu, A; Schröder, T; Nikki, P; Mäkelä, P H; Lempinen, M
Abstract : Enterobacterial common antigen is a highly immunogenic component of the Gram negative bacterial cell wall that is common to all enteric bacteria. In the present study, the humoral antibody response against enteric bacteria was investigated by measuring antibodies to enterobacterial common antigen in paired serum samples in 38 patients with acute pancreatitis and in 31 healthy subjects. In mild pancreatitis (11 patients), no changes in anti-enterobacterial common antigen titres were observed as compared with healthy controls. Nine of the 10 patients had a significant increase (greater than or equal to 8 times) in anti-enterobacterial common antigen titres during the disease. Similarly, in patients with fulminant (haemorrhagic) pancreatitis who survived, a significant increase in anti-enterobacterial common antigen titres occurred during the course of the disease (in nine of the 11 patients). Paradoxically, only one of the six patients with fulminant pancreatitis with fatal outcome showed a significant increase in his anti-enterobacterial common antigen titre. The results suggest that Gram negative bacterial components escape into the systemic circulation in acute pancreatitis. This may have pathophysiologic significance in this disease.